Between Rights and Reality: "Access to Social Protection for Informal Workers in Nepal" - Kunwor, Bina; Chhetri, Sankalpa (KDCBAR Law Journal, 2025)
Informal workers constitute a significant portion of Nepal’s labor force, yet they remain excluded from formal social protection systems. Over 80 percent of the total labor force is engaged in the informal sector. Despite contributing significantly to the national economy, they have not received adequate legal recognition and institutional protection. The study explores the critical gap between the constitutional and policy-level recognition of social protection as a right and the actual accessibility of these provisions for informal workers in Nepal. Drawing on a review of existing legal frameworks and other secondary data the paper analyzes the legal, institutional and socio-economic barriers that hinder inclusive social protection. The paper argues for a rights-based, inclusive and context-sensitive approach to social protection that addresses the specific vulnerabilities of informal workers. It concludes with recommendations to enhance policy coherence, expand coverage and ensure participatory governance to realize the transformative potential of social protection in promoting equity and resilience in Nepal’s labor market.